Low Temperature-Induced Cytoplasmic Acidosis in Cultured Mung Bean (Vigna radiata [L.] Wilczek) Cells. - Yoshida, S. (1994)
Cold-induced changes in vivo in the cytoplasmic pH of suspension-cultured cells of mung bean (Vigna radiata [L.] Wilczek) were investigated by fluorescence-ratio imaging cryomicroscopy with special reference to the variations in the chilling sensitivity of cells during the growth cycle. Because of the preferential localization of the fluorophore in the cytoplasm under specified conditions and the ideal response of fluorescence to pH, fluorescein diacetate allows measurements to be made of temporal changes in cytoplasmic pH at low temperature. A remarkable difference was demonstrated in the cold-induced changes in cytoplasmic pH between cells at the early and late stages of exponential growth. The cells at the early stage of exponential growth were most sensitive to chilling, and the cytoplasmic pH decreased dramatically within a short period of incubation at 0[deg]C, decreasing from 7.4 to 6.8 after 4 h and to 6.3 after 18 h. The cells at the late stage of exponential growth were chilling tolerant, and no significant decrease in the cytoplasmic pH was observed during the incubation at 0[deg]C for 24 h or even longer. From the results presented here, it appears that cold-induced cytoplasmic acidosis is characteristic of chilling-sensitive mung bean suspension-cultured cells.